Analisis Kadar Air dan Kadar Abu Briket Lumpur IPAL dan Fly Ash dengan Penambahan Serbuk Gergaji Kayu - Milenia Yayi Prameswari Setyono; Yayok Suryo Purnomo (Yayasan Literasi Sains Indonesia, 2022)
WWTP sludge which is the result of industrial wastewater treatment that has the potential for environmental pollution that must be managed by the industry concerned. utilization of waste sludge into briquettes can be an alternative that needs to be reviewed in order to improve energy efficiency. The purpose of this study was to determine the IPAL mud, fly ash, and wood sawdust can be used as alternative fuels in the form of briquettes, to determine the effect of variations of IPAL mud, fly ash, and wood sawdust on the quality of briquettes in the form of ash content and moisture content. Based on the results of the research that has been carried out, it can be concluded that the raw materials for WWTP mud, fly ash, and wood sawdust can be used as raw materials for making briquettes according to SNI 4931-2010 with type B briquette classification. All briquettes produced are included in the set standards because all briquettes research results show a figure of <5% which is certainly below the established quality standard, which is 12% in each briquette produced. Briquettes of a mixture of sewage sludge, fly ash, and sawdust with a concentration of 40%: 30%: 30% and an adhesive percentage of 20% have the highest ash content in each percentage of molasses.